Study of the permittivity, permeability and microwave attenuation of zinc ferrites nanoparticles prepared by sol-gel methods - Ibrahim Abbas, Sabah; Salam Khamas, Abbas (International Journal of Engineering and Technology, 2019)
Zinc ferrite nanoparticles is synthesized by the sol-gel method from Zn (NO3)2.6H2O and Fe (NO3)3.9H2O by using molar concentrations (0.2M and 0.4M), and all samples were sintered at temperatures (600 Â°C, 800Â°C and 1000 ) for two hours. X-ray diffraction patterns reveal the presence nanoparticles of cubic spinel phase of zinc ferrite structure with a mix of other phases are a hexagonal hematite type of Î±-Fe2O3 and the hexagonal wurtzite structure of ZnO. Morphology characteristic has been examined by using the scanning Probe Microscope and shown the grain size is increasing when the molar concentration increases probably due to the large radius of zinc ions than . Complex permeability, complex permittivity, and attenuation of zinc ferrite composite are investigated in X-band frequency. The real part of magnetic permeability decreases with increasing frequency because the external field changes rapidly at high frequency and the Magnetic loss is very low due to reduce the eddy current. The real and imaginary parts of the permittivity remains nearly constant and low values with increasing frequency for concentrations 0.2M and 0.4M at sintering temperature 600â„ƒ. The constant values for real part of permittivity means there was a dominant one type of polarization. The low values of imaginary part of permittivity may be due to decrease of dipole polarization. The best desired absorbance and attenuation of microwave can be achieved at the low values of the sintering temperature (600 ) for two concentration where the reflectivity of the waves at the minimum value. Â Â Â